The Potential of Mobile Learning in Improving Students' Intention and Learning Readiness in Higher Education: A Systematic Literature Review Using PRISMA - Sitti Saum Sayidaturrahmah; Ponasari Baron Mutiara Kenya; Ahkamsyadid Yusmaputra Salim; Tantradiva Noftyandikumara Adicitadharma; Citra Kurniawan; Rumaizah Mohd Nordin (PAEDAGOGIA, 2025)
In the modern technological era, mobile learning offers students enhanced flexibility and accessibility in education. However, Issues that impedes the implementation of mobile learning is the lack of student readiness to use this technology effectively, both in terms of technological skills and psychological readiness. In addition, there is still a gap in understanding the factors that influence students' intention and learning readiness in various higher education contexts. This study aims to explore the potential of mobile learning in improving students' learning intention and readiness. The method used is a Systematic Literature Review with a descriptive qualitative approach, following the PRISMA guidelines. Articles were collected from Google Scholar, Scopus, and Emerald Insight databases with the search keywords “mobile learning,” “students' intention,” and “learning readiness,” covering publications from 2020 to 2024. The review process involved selection based on inclusion and exclusion criteria and thematic analysis of study results. This study found that students perceived the ease of use and technology benefits are the most important elements driving m-learning acceptance. Technology skills, psychological readiness, social support, perceived utility, convenience, and task-material compatibility are the important elements influencing students' learning intention and readiness. These findings are expected to guide the development of more effective technology-driven learning methodologies, particularly within Indonesian higher education. They also underscore the potential of mobile devices to enhance learning efficiency and enable personalized learning approaches tailored to individual needs